2014
DOI: 10.1177/230949901402200328
|View full text |Cite
|
Sign up to set email alerts
|

Total Sacrectomy for Low-Grade Malignant Peripheral Nerve Sheath Tumour: A Case Report

Abstract: We report on a 58-year-old woman who underwent total sacrectomy and spinopelvic reconstruction for a low-grade malignant peripheral nerve sheath tumour involving the sacrum. One week later, she developed deep wound infection, and the entire spinopelvic reconstruction was removed. At the 36-month followup, the patient had no pain and was able to walk with a walking frame. There was no sign of recurrence or metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Because of lower complication rates, other authors advocate sacrectomy without reconstruction [11,19,21,22]; at least one study suggested little difference between patients who had a reconstruction and those who had not [24]. We previously reported a satisfactory result of ambulatory status of a patient after total sacrectomy without spinopelvic reconstruction and thought that it was an appropriate method in selected patients [17]. Although others have evaluated total sacrectomy without spinopelvic reconstruction [11,19,21,22,24], those reports lacked detail on postoperative functional outcomes, especially with respect to resection location.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of lower complication rates, other authors advocate sacrectomy without reconstruction [11,19,21,22]; at least one study suggested little difference between patients who had a reconstruction and those who had not [24]. We previously reported a satisfactory result of ambulatory status of a patient after total sacrectomy without spinopelvic reconstruction and thought that it was an appropriate method in selected patients [17]. Although others have evaluated total sacrectomy without spinopelvic reconstruction [11,19,21,22,24], those reports lacked detail on postoperative functional outcomes, especially with respect to resection location.…”
Section: Discussionmentioning
confidence: 99%
“…For nine patients with bilateral Type I resection, five were able to walk without walking aids, four needed a walking aid and the mean MSTS score was 20 (range, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Among the five patients who had a Type I resection on one side and a Type II resection on the contralateral side, four were able to walk with a walking aid, and the mean MSTS score was 18 (range, [15][16][17][18][19][20][21][22]. Radiographic findings in patients who had bilateral Type I resections where part of the anterior sacroiliac joint was remained (Fig.…”
Section: Influence Of Resection Location On Ambulatory Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…En bloc sacrectomy can be an effective treatment for sacral tumors, metastatic lesions, and conditions such as osteomyelitis. 15 However, partial or total removal of the sacrum results in extensive injury to surrounding bone and soft tissue, often requiring hardware for bony reconstruction and soft-tissue coverage via pedicled or free flaps. 69 Plastic surgeons face particularly challenging decisions in this setting, as wound closure is frequently complicated by radiation, compromised local vasculature, and inherent stress to the sacral region.…”
Section: Introductionmentioning
confidence: 99%